Analisis kejadian Indeks Standar Pencemaran Udara (ISPU) sebagai informasi mutu udara di Kota Pekanbaru - Ratna Masni, Fenny; Herniwanti (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2025)
Air quality problems that occur in the world today are always associated with the development of large cities and almost no large city in the world is free from symptoms of air pollution. The level of air quality is getting lower day by day due to high levels of air pollution. Pekanbaru City is one of the cities in Indonesia that is prone to air pollution. This research aims to analyze the incidence of the Air Pollution Standard Index (ISPU) as information on air quality in Pekanbaru City. The research method used was collecting primary and secondary data through informants. The research was conducted at the Pekanbaru City Environment and Hygiene Service. Data were analyzed using the fishbone method and the Urgency, Seriousness, Growth (USG) method. The research results show that forest fires are the main priority problem which causes the air pollution standard index (ISPU) in Pekanbaru City to be in the medium category. The conclusion of this research is that forest fires often occur in Pekanbaru City which then causes smog and disrupts air quality, increases pollution levels, and increases the risk of respiratory problems.